Trans-Reality Television : the Transgression of Reality, Genre, Politics, and Audience. - Carpentier (Lexington Books, 2012)
Trans-Reality Television offers an overview of contributions which engage with the phenomenon of reality television as a tool to reflect on societal and mediated transformations and transgressions. The chapters in this volume are divided into four sections, all of which deal with how we see the fluid social at work in reality television through the trans-real, trans-politics, trans-genre, and trans-audience.